Becoming in STEM: Developing a Culture of Criticality in the Space Between Person and Institution - Calabrese Barton, Angela; Tan, Edna; McDaniel, Autumn (Frontiers in Education, 2020)
This paper presents a single case study of a youth, Fall, tracing her STEM engagement from grade 5 through high school, across STEM spaces both formal and informal, utilizing critical, longitudinal ethnography. Drawing from social practice and critical justice theories, we present how Fall’s STEM history-in-person collided with the history-in-institutional-struggles, as a white girl growing up in multigenerational poverty who eagerly engaged in what she calls “science that matters.” We present how Fall enacted commitments-in-practice, in conjunction with three related, local contentious practices, leading to the emergence of a culture of criticality. We theorize how the space between person and institution became and functioned as an incubating space, supporting Fall’s authoring of a new chapter in her STEM history-in-person.